Andrei Tarkovsky, Kazimierz Kutz and Federico Fellini: References and counterpoints. Issue 3 (1st June 2023) - Shrager, Miriam; Matskevich-Levin, Natalia
This article provides a detailed analysis of references to other films found in two of Andrei Tarkovsky's works, thus highlighting the films' intertextual and intermedial nature. More specifically the article examines several referential elements found in Tarkovsky's Ivanovo detstvo ( Ivan's Childhood ) (1962 ) andZerkalo ( Mirror ) (1975), which, as scholars suggest, borrow elements from Kazimierz Kutz's Krzyż Walecznych ( Cross of Valour ) (1958 ) and Federico Fellini's 8½ (1963 ), respectively. Through the theoretical analysis of filmmaking techniques as well as intertextual analysis, the article seeks to explain why and how Tarkovsky employs these references in his films. The article therefore examines the cinematography of the three directors in addition to their films' visual stylistics and formal elements. By analysing mise en scènes, types of shots, lighting, editing and more, the article proves that the references Tarkovsky employs in his two films not only justify connections to his films' main ideas but also serve as incontrovertible evidence that his films contain references and counterpoints to Kutz's and Fellini's works.